2018
DOI: 10.12659/aot.906658
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes Using a Drug-Coated Balloon for Transplant Renal Artery Stenosis

Abstract: BackgroundThis study aimed to evaluate the early and mid-term outcomes of drug-coated balloon (DCB) use in patients who underwent intervention for transplant renal artery stenosis (TRAS).Material/MethodsWe retrospectively reviewed the records of TRAS patients who received endovascular therapy with DCB in our institution from March 2016 to January 2017. Statistical analysis of pre-/postoperative levels of serum creatinine (Scr), systolic blood pressure (SBP), and renal artery peak systolic velocities (PSV) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Several studies have suggested that PTAS provides excellent clinical results and have recommended the use of stenting as an initial treatment for TRAS . However, a study conducted by Li et al showed that drug‐coated balloon alone can also be very effective in restoring blood flow to the graft and maintaining its function. In our experience, if the stenosis is short, linear, or relatively distal from the anastomosis, PTA can also achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have suggested that PTAS provides excellent clinical results and have recommended the use of stenting as an initial treatment for TRAS . However, a study conducted by Li et al showed that drug‐coated balloon alone can also be very effective in restoring blood flow to the graft and maintaining its function. In our experience, if the stenosis is short, linear, or relatively distal from the anastomosis, PTA can also achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous interventional therapy is widely accepted as a viable therapy for TRAS . However, the benefits of endovascular interventional therapy to correct TRAS remain controversial.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations